2020
DOI: 10.1186/s12885-020-07640-4
|View full text |Cite
|
Sign up to set email alerts
|

Cancer of unknown primary with EGFR mutation successfully treated with targeted therapy directed by clinical next-generation sequencing: a case report

Abstract: Background Cancer of unknown primary (CUP) is usually treated with nonselective and empirical chemotherapy; however, its prognosis is generally poor, with a median survival of less than a year. Thus, clinicians eagerly await the development of more effective treatment strategies. In recent years, advances in next-generation sequencing (NGS) have made it possible to analyze comprehensively the genome of individual cancers. NGS has identified many genomic alterations, some of which are potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…19,20 Mitani et al reported successful treatment of a CUP patient with EGFR mutations under the guidance of NGS, achieving long-term disease control. 21 Here, we report a unique case of a CUP patient carrying a germline BRCA1 pathogenic mutation R71K, whereas the application of the PARP inhibitor olaparib has achieved good therapeutic effects. Although we performed extensive pathological examinations (eg, H&E stain and immunohistochemistry) and imaging technologies (eg, CT, MRI, and PET-CT scan), the primary site has not yet been identified, while additional workup such as direct internal organ visualization by an exploratory laparotomy may facilitate a definitive diagnosis.…”
Section: Discussionmentioning
confidence: 93%
“…19,20 Mitani et al reported successful treatment of a CUP patient with EGFR mutations under the guidance of NGS, achieving long-term disease control. 21 Here, we report a unique case of a CUP patient carrying a germline BRCA1 pathogenic mutation R71K, whereas the application of the PARP inhibitor olaparib has achieved good therapeutic effects. Although we performed extensive pathological examinations (eg, H&E stain and immunohistochemistry) and imaging technologies (eg, CT, MRI, and PET-CT scan), the primary site has not yet been identified, while additional workup such as direct internal organ visualization by an exploratory laparotomy may facilitate a definitive diagnosis.…”
Section: Discussionmentioning
confidence: 93%
“…A total thyroidectomy was performed, and genetic profiling of the specimen revealed L858 and T790M EGFR mutations. Therapy was adjusted from erlotinib to osimertinib (another epidermal growth factor receptor tyrosine kinase for specific EGFR mutation) based on this, which resulted in clinical improvement [ 106 ]. In another case report, a patient with metastatic uveal melanoma to the thyroid was found to have BRAF mutation wild type [ 99 ].…”
Section: Treatmentmentioning
confidence: 99%
“…The emergence of L858R as a potential biomarker holds promise for predicting the responsiveness of lung cancer models to anti-EGFR therapy ( Marrocco et al, 2023 ). Notably, the use of epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) has demonstrated considerable efficacy in NSCLC patients harboring this mutation, offering a favorable side effect profile and contributing to an improved quality of life ( Mitani et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%